Atmospheric electrification in the solar system - Aplin, K (2006)
Atmospheric electrification is not a purely terrestrial phenomenon: all Solar System planetary atmospheres become slightly electrified by cosmic ray ionisation. There is evidence for lightning on Jupiter, Saturn, Uranus and Neptune, and it is possible on Mars, Venus and Titan. Controversy surrounds the role of atmospheric electricity in physical climate processes on Earth; here, a comparative approach is employed to review the role of electrification in the atmospheres of other planets and their moons. This paper reviews the theory, and, where available, measurements, of planetary atmospheric electricity which is taken to include ion production and ion-aerosol interactions. The conditions necessary for a planetary atmospheric electric circuit similar to Earth's, and the likelihood of meeting these conditions in other planetary atmospheres, are briefly discussed. Atmospheric electrification could be important throughout the solar system, particularly at the outer planets which receive little solar radiation, increasing the relative significance of electrical forces. Nucleation onto atmospheric ions has been predicted to affect the evolution and lifetime of haze layers on Titan, Neptune and Triton. Atmospheric electrical processes on Titan, before the arrival of the Huygens probe, are summarised. For planets closer to Earth, heating from solar radiation dominates atmospheric circulations. However, Mars may have a global circuit analogous to the terrestrial model, but based on electrical discharges from dust storms. There is an increasing need for direct measurements of planetary atmospheric electrification, in particular on Mars, to assess the risk for future unmanned and manned missions. Theoretical understanding could be increased by cross-disciplinary work to modify and update models and parameterisations initially developed for a specific atmosphere, to make them more broadly applicable to other planetary atmospheres. © Springer 2006.